Synthesis of chiral N-phosphoryl aziridines through enantioselective aziridination of alkenes with phosphoryl azide via Co(II)-based metalloradical catalysis - Tao, Jingran; Jin, Li-Mei; Zhang, X. Peter (Beilstein Journal of Organic Chemistry, 2014)
The Co(II) complex of a new D2-symmetric chiral porphyrin 3,5-DiMes-QingPhyrin, [Co(P6)], can catalyze asymmetric aziridination of alkenes with bis(2,2,2-trichloroethyl)phosphoryl azide (TcepN3) as a nitrene source. This new Co(II)-based metalloradical aziridination is suitable for different aromatic olefins, producing the corresponding N-phosphorylaziridines in good to excellent yields (up to 99%) with moderate to high enantioselectivities (up to 85% ee). In addition to mild reaction conditions and generation of N2 as the only byproduct, this new metalloradical catalytic system is highlighted with a practical protocol that operates under neutral and non-oxidative conditions.
Keywords: asymmetric aziridination; aziridine; chiral porphyrin; cobalt complex; metalloradical catalysis; organophosphorus; phosphoryl azide